Formulation and Evaluation of Solid Dispersion Chitosan Tablet from Whiteleg Shrimp (Litopenaeus vannamei) Using PVP K-30 As a Carriers - Hilya Nur Imtihani; Fitria Abbas Thalib; Silfiana Nisa Permatasari (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2021)
Whiteleg shrimp (Litopenaeus vannamei) on the market are processed or sold only to take part in the meat. The head, shell, and tail are thrown away without any prior processing. Underutilized waste causes environmental problems. An alternative to overcome this environmental disturbance phenomenon is to utilize shrimp shells containing chitin and subsequently transformed into chitosan that can be applied in various fields. Chitosan has poor solubility in water but high permeability; thus, improve bioavailability is accomplished by making solid dispersions. This study aims to formulate and evaluate the solid dispersion tablet using chitosan extract from L. vannamei as an active agent with PVP K-30 as a carrier. The formulation divided into three groups, that was F1 (chitosan : PVP K-30 = 1 : 1 solid dispersion), F2 (chitosan : PVP K-30 = 1 : 3 solid dispersion), and F3 (pure chitosan). The result of chitosan solid dispersion was molded into tablets by the direct compression method. The tablets were evaluated by weight and size uniformity, hardness, friability, and disintegration time. All the formulas by weight and size uniformity as well as disintegration time fulfill the requirements. The hardness of the tablets from F3 with 4,275 kg was the best from F1 and F2. By statistic analytical from weight uniformity, hardness and disintegration time give significant difference with sig. <0.05.